Mechanism of TH2/TH17-predominant and neutrophilic TH2/TH17-low subtypes of asthma - Liu, Weimin; Liu, Sucai; Verma, Mukesh; Zafar, Iram; Good, James T.; Rollins, Donald; Groshong, Stephen; Gorska, Magdalena M.; Martin, Richard J.; Alam, Rafeul (Journal of allergy and clinical immunology, 2017)
The mechanism of TH2/TH17-predominant and TH2/TH17-low asthma is unknown. We sought to study the immune mechanism of TH2/TH17-predominant and TH2/TH17-low asthma. In a previously reported cohort of 60 asthmatic patients, 16 patients were immunophenotyped with TH2/TH17-predominant asthma and 22 patients with TH2/TH17-low asthma. We examined bronchoalveolar lavage (BAL) fluid leukocytes, cytokines, mediators, and epithelial cell function for these asthma subgroups. Patients with TH2/TH17-predominant asthma had increased IL-1β, IL-6, IL-23, C3a, and serum amyloid A levels in BAL fluid, and these correlated with IL-1β and C3a levels. TH2/TH17 cells expressed higher levels of the IL-1 receptor and phospho-p38 mitogen-activated protein kinase. Anakinra, an IL-1 receptor antagonist protein, inhibited BAL TH2/TH17 cell counts. TH2/TH17-low asthma had 2 distinct subgroups: neutrophilic asthma (45%) and pauci-inflammatory asthma (55%). This contrasted with patients with TH2/TH17-predominant and TH2-predominant asthma, which included neutrophilic asthma in 6% and 0% of patients, respectively. BAL fluid neutrophils strongly correlated with BAL fluid myeloperoxidase, IL-8, IL-1α, IL-6, granulocyte colony-stimulating factor, and GM-CSF levels. Sixty percent of the patients with neutrophilic asthma had a pathogenic microorganism in BAL culture, which suggested a subclinical infection. We uncovered a critical role for the IL-1β pathway in patients with TH2/TH17-predminant asthma. A subgroup of patients with TH2/TH17-low asthma had neutrophilic asthma and increased BAL fluid IL-1α, IL-6, IL-8, granulocyte colony-stimulating factor, and GM-CSF levels. IL-1α was directly involved in IL-8 production and likely contributed to neutrophilic asthma. Sixty percent of neutrophilic patients had a subclinical infection. [Display omitted]